2016
DOI: 10.22178/pos.17-13
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Impact of Residential Neighbourhood Crime on Housing Investment Using Logistic Regression

Abstract: Abstract. This paper discusses the impact of criminal activities on residential property value. With regard to criminal activities, the paper emphasizes on the contribution of each component of property crime. One thousand (1000) sets of structured questionnaire were administered on the residents of residential estates within the South Western States of Nigeria out of which 467 were considered useable after the data screening. Purposive and systematic sampling techniques were used while logistic regression was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Findings from the study revealed that property value in the gated community is higher than that of non-gated community. Olajide and Lizam (2016) assessed the impact of residential neighbourhood crime on residential property value. Findings from the study revealed that neighbourhood crime have a negative impact on residential property value.…”
Section: Factors Associated To Property Valuesmentioning
confidence: 99%
“…Findings from the study revealed that property value in the gated community is higher than that of non-gated community. Olajide and Lizam (2016) assessed the impact of residential neighbourhood crime on residential property value. Findings from the study revealed that neighbourhood crime have a negative impact on residential property value.…”
Section: Factors Associated To Property Valuesmentioning
confidence: 99%
“…The work extends the neighborhood factors in Aliu (2023) beyond security, which means that other factors apart from security have tendencies to negatively affect residential property values and create unscheduled and unintended residential mobility. Moreover, this work and others surveyed are unanimous that security determines the land value, property value, or rent, as seen in Olajide and Lizam (2016), Nigeria (Bamiteko and Adebiyi, 2020), and South Africa (Odubiyi et al, 2019). However, it appears that natural disasters like flooding can attenuate the land value, despite the three attributes considered in his paper.…”
Section: Discussionmentioning
confidence: 73%
“…This finding is in consonance with the study of Aliyu et al (2011) and Uroko (2018) that opined that ethno-religious crisis had negative impact on property value. In addition, Frischtak and Mandel (2012), Olajide and Lizam (2016), Effiong (2018), Yoade and Olatunji (2018) among others also opined that crime have negative effect on property values. However, there is a slight divergent from the current study’s finding in the area of types of violence identified in the study area which are political, ethnic, religious, kidnapping and terrorism.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Urban violence can also be in form of rape, robbery, arson and shooting. A significant cause of urban violence in recent times is terrorism from activities of organized terrorist groups such as Al-Qaeda and Islamic State of Iraq and Syria' (ISIS), to religious wars, tribal clashes and political upheavals in many parts of the world (Isaac, 1994; Olajide and Lizram, 2016). In Nigeria particularly, this includes the Boko Haram insurgency and the Fulani herdsmen crises.…”
Section: Introductionmentioning
confidence: 99%